STUDENTS’ MATHEMATICAL CONCEPT CONSTRUCTION ERRORS IN EXPONENT MATERIAL BASED ON MATHEMATICS ANXIETY - nur hayati; Rita Lefrida; Mubarik Mubarik; Fajriani Fajriani (FKIP Universitas Muhammadiyah Tangerang, 2026)
This study aims to describe errors in the construction of mathematical concepts related to exponents in light of mathematics anxiety. This study employs a qualitative approach with two subjects, students with low and high levels of mathematics anxiety. Data analysis uses an iterative model consisting of data condensation, data presentation, and drawing conclusions. The results of the study show that students with low mathematics anxiety exhibit pseudo constructions “incorrect” that is, they provide incorrect answers but are able to correct them after reflection, construction holes in the form of correct answers that are not supported by a complete conceptual understanding, and illogical constructions involving reasoning that does not align with the concept of exponents. Meanwhile, students with high levels of mathematics anxiety exhibited conceptual construction holes because they were not yet able to fully grasp the concept of exponents. Mis-analogical construction involved the use of inappropriate analogies when applying the properties of exponents, while mis-logical construction involved flawed reasoning when solving problems involving exponents. The research findings indicate differences in the types of errors in mathematical concept construction based on students’ levels of mathematics anxiety